A fuzzy integrated SPC/APC scheme for optimised levels of process quality, performance and robustness. (1st January 2011) - Saif, Abdul-Wahid A.; Akram, Muneeb A.; Abdur Rahim, M.
Statistical process control ( SPC ) and automatic process control ( APC ) are two independent methods for quality improvement and process adjustment that have been developed in isolation from each other and applied within different industries. Both methods were initially considered to be in conflict with each other, until their advocates realised the fact that the techniques being applied were complementary rather than being contradictory. Since then, some work suggesting integration between SPC and APC techniques has appeared in the literature. Most integration strategies found in the literature applied SPC techniques for monitoring and APC techniques for process regulation, while others derived SPC controllers and applied their use alone, which does not imply complete integrated schemes. Our objective in this work is to develop an integrated scheme that combines the utilisation of SPC and APC techniques for process monitoring, as well as its adjustment under fuzzy logic interaction. We envision that driving any process under the proposed scheme will optimise its level of quality and performance, as well as robustness. To illustrate the effectiveness of the proposed scheme, we will conduct an optimisation case study on a pH control process.